All Days 1993
DOI: 10.2118/26604-ms
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Measurement and Prediction of Paraffin Precipitation in Crude Oil

Abstract: Economically and technically viable methods for controlling paraffin buildup in pipelines and wellbores are critical to the production of crude oil in deep water and cold environments. Conoco has identified laboratory test methods and developed a paraffin prediction program to better quantify the paraffin (wax) deposition potential of a crude oil and to evaluate or develop methods of preventing or controlling paraffin buildup. This paper will describe the thermodynamic paraffin model and the complementary labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 1 publication
1
34
0
2
Order By: Relevance
“…It is also possible that for low wax content crude oils, WAT and/or the presence of paraffin crystals may go completely undetected by viscometry, DSC and/or LT, leaving the investigator unaware of potential waxing problems. The CPM is generally deemed to be the most sensitive and the only direct visual technique applicable for all non-biodegraded oils including opaque fluids Erickson et al, 1993).…”
Section: Cloud Point Measurement Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that for low wax content crude oils, WAT and/or the presence of paraffin crystals may go completely undetected by viscometry, DSC and/or LT, leaving the investigator unaware of potential waxing problems. The CPM is generally deemed to be the most sensitive and the only direct visual technique applicable for all non-biodegraded oils including opaque fluids Erickson et al, 1993).…”
Section: Cloud Point Measurement Techniquesmentioning
confidence: 99%
“…(Erickson et al, 1993;Coutinho et al, 2001) or may be described using a free energy model (Won, 1986;Hansen et al, 1988;Coutinho et al, 1996;Lira-Galena et al, 1996). For high pressure systems (live oils), on the other hand, the liquid phase is generally described using an Equation of State (Lira-Galena et al, 1996;Pan et al, 1997;Pauly et al, 2000).…”
Section: Thermodynamic Models For Petroleum Waxmentioning
confidence: 99%
See 1 more Smart Citation
“…Crude oil WPT has been measured using conventional experimental methods such as differential scanning calorimetry (DSC) [4][5][6][7][8], viscometry [5][6][7][8][9][10], near-IR spectroscopy (NIR) [11] and cross-polarized microscopy (CPM) [5,7,[12][13][14][15]. The measurement of WPT by DSC is explained in detail in a later section in this report.…”
Section: Summary Of Wpt Measurement Methodsmentioning
confidence: 99%
“…Wax precipitates from crude oil when the operating temperature is at or below the WAT (cloud point temperature). It has been reported that wax deposition will not occur until the operating temperature falls to or below the WAT (Erickson et al, 1993). All other factors actually lead to wax deposition when the temperature is already at or below the cloud point.…”
Section: Temperaturementioning
confidence: 99%